The Influence of Profitability on an Enterprise's Capital Structure - The Example of Joint-stock Companies Listed on the Warsaw Stock Exchange - Jerzemowska, Magdalena; Hajduk, Agnieszka (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents an analysis of the relationship between a company's capital structure and its profitability. Current theories of capital structure suggest that such a relationship exists, but there is no agreement as to where it may lead. The Pecking Order Theory predicts that high profitability is accompanied by a lower level of debt. Signalling Theory, on the other hand, holds that the relationship between a company's profitability and its debt will be positive. The paper attempts to determine which of these two theories is supported by the Polish circumstances through the prism factor: the profitability of the company. The study uses the financial statements of 196 companies listed on the Stock Exchange in Warsaw and was carried out for two macro-sectors: industry, and trade and Services. Multiple linear regression method was used for the empirical analysis. A positive relationship is shown between the capital structure and profitability of companies in the Trade and Services macro-sectors.